(untitled) (International Journal of Bamboo and Rattan, 2023)
Woody bamboos are wonderful replacement for tropical hardwood trees because of their short growth cycles and a high carbon dioxide exchange rate; they are capable of promoting avoided tropical deforestation. This article aims at analysing the usefulness of bamboo-based landscape restoration programmes, agroforestry systems and appropriate technologies towards improving sustainable food security while at the same time contribute to reclaiming degraded soils, boost bamboo product manufacturing, and supplement animal feeds. The outcomes of this paper would further contribute to improving climate resilience and livelihoods at households and community levels in Central and West Africa. Logically, the first expected approach is to highlight relevance of Nnamdi Azikiwe University (UNIZIK)-based bamboo research platform known as the Sahelian Institute for Bamboo Research and Entrepreneurship Development (SIBRED), which is established to build capacities and share knowledge on contemporary bamboo related innovations available within Sahelian Africa Countries and their neighbours. Using the UNIZIK-based SIBRED as an outreach platform, we hope to strengthen relationships with local communities, government agencies, non-governmental organisations and bamboo value chain investors at both domestic and international levels. Thus contributing to achieving some of the 17 United Nations Sustainable Development Goals (SDGs) as well as support the realization of a stronger green industrial growth and entrepreneurship education in Central and West Africa. Therefore, the outcomes from this paper would serve as reference materials that can support the development of policy responses, at regional, national or catchment scale, to existing and emerging environmental related problems using bamboo nature based solution (NBS) through partnership with SIBRED.